A crawling peg system for raw materials - Dietrich Kebschull (Intereconomics, 1976)
Weighty objections have been raised against stabilization of commodity markets through agreements. The drawbacks of commodity agreements can, however, be largely overcome if the rigid theoretical notion of a price fixed strictly for a long period is abandoned.
Keywords: 330; Raw Materials